2014
DOI: 10.1109/tmag.2013.2278397
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Normal Force Characteristics of a Permanent Magnet Linear Synchronous Motor with Double Primary Side

Abstract: The large normal force of the permanent magnet linear synchronous motor (PMLSM) is caused by the PM group shifting. This is the significant drawback which will deteriorate the performance of the drive system in high-precision applications. In the optimization design process, when the PM group shifting length is not zero the normal force will be changed into a pulsation curve with large amplitude. To solve this problem, this paper proposes that the PMLSM is divided into two symmetrical PMLSMs. The effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In the PMLSM optimisation design, DOE can be used to explore the effects of various structure parameters on motor thrust and thrust ripple [29]. The method proposed in this paper is one of DOE, which is commonly known as Taguchi optimisation method; this method is one of those that use orthogonal array to screen the experimental conditions and means [30], the advantage of this method is that it uses the least experimental data based on the number of factors and levels in factor parameter space to achieve the best combination of parameter design and optimal results. Four undetermined factors exist, namely, h , δ , τ , and d , and each factor has three levels [31].…”
Section: Taguchi Optimisation Methodsmentioning
confidence: 99%
“…In the PMLSM optimisation design, DOE can be used to explore the effects of various structure parameters on motor thrust and thrust ripple [29]. The method proposed in this paper is one of DOE, which is commonly known as Taguchi optimisation method; this method is one of those that use orthogonal array to screen the experimental conditions and means [30], the advantage of this method is that it uses the least experimental data based on the number of factors and levels in factor parameter space to achieve the best combination of parameter design and optimal results. Four undetermined factors exist, namely, h , δ , τ , and d , and each factor has three levels [31].…”
Section: Taguchi Optimisation Methodsmentioning
confidence: 99%
“…In Ansoft, the x-axis negative direction is the motion direction of the platform, and the positive direction of the y-axis is the floating direction. The two motor models are respectively divided, and the boundary conditions are set and solved [26]. Figure.…”
Section: Finite Element Calulationmentioning
confidence: 99%
“…The result shows that without optimization, the detent force caused by the end effect is much higher than that caused by the slot effect. The ways to reduce the detent force can be classified into two kinds, one is the sophisticated control strategies of the machines [13][14][15][16], and the other is the optimization of the machine structure [17][18][19][20][21][22][23][24][25], as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…[18] analyzed the influence of the primary side length on the detent force, and indicated that the detent force can be greatly reduced by optimization of the length. [19] developed a multiple secondary side PMLSM to reduce the detent force, while [20] developed a multiple primary side PMLSM to reduce the detent force. Auxiliary poles or auxiliary teeth are also widely used to reduce the detent force [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%